Prevalence of co-infection with Ehrlichia spp. or Theileria spp. in dogs naturally infected with babesiosis in the Eastern Cape - Schoeman, Johan P. (University of Pretoria, 2025)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2025.